Prædiken og profeti hos de første kvækere - Gregersen, Susanne (Religionsvidenskabeligt Tidsskrift, 1994)
Early quakerism at a time when orthodoxy and uniformity were met by an insistence on the right of individual religious convictions and affiliations. In this time of tension the early quakers' prohpetic awareness of being the tools of God in his last great plan for his people resulted in the fol´lowing reactions from contemporary orthodox puritanism: 1) They were madmen, 2) They were politically dangerous, 3) they spoke against the Word of the Bible and therefore instruments of Satan. The article illustrates by examples from the prophetic ministry among the first Publishers of Truth what this means to their view of the Bible and their message. The direct theological danger was that of antinomianism, and the theological consequence was therefore a necessary establishing of authority without disregarding the Inner Light. This was done by renouncing man's free will, by referring to their religious experiences and insights as common and not individual, and through consensus in all important matters. It also led to the building up of a society with a fixed framework such as an Elder-institution. In the long run the self-consideration led ot a weakening of the prophetic element within quakerism, but never of the respect for the Inner Light in every man, and the equality in faith and the plurality in its expression, which grew out of the same prophetic faith.